The Predictors of Unmet Demand for Unions in Non-Union Workplaces: Lessons from Australia - Pyman, Amanda; Teicher, Julian; Cooper, Brian; Holland, Peter (Relations industrielles / Industrial Relations, 2017)
In this study, we examine the predictors of unmet demand for unions in non-union workplaces, using the Australian Worker Representation and Participation Survey (AWRPS). Unmet demand is defined here, as those employees in non-union workplaces who would be likely to join a union if one were available. We argue that this is the first study in Australia to examine the predictors of unmet demand in non-union workplaces, and, that this is an important line of inquiry given a rise in non-union workplaces and never members in Australia, alongside declining union density and membership numbers. Drawing on three strands of existing literature, namely the individual propensity to unionize, the rise and characteristics of non-union workplaces and alternative forms of representation, and, managerial responsiveness to employees and unions, we develop and test four hypotheses.Our results show, controlling for a range of personal, job and workplace characteristics, that there are two significant predictors of the willingness to join a union in non-union workplaces: perceived union instrumentality (Hypothesis 2) and perceived managerial responsiveness to employees (Hypothesis 4), whereby employees who perceive that managers lack responsiveness are more likely to want to join a union if one were available.These results show that unions must try to enhance their instrumentality in workplaces and could be more effective in recruiting if they targeted never members. The results also show that unions need to have some gauge (measure) of how responsive managers are to employees, and that they can leverage poor responsiveness of managers for membership gain and the extension of organizing. In the final analysis, an understanding of the predictors of unmet demand for unions in non-union workplaces has implications for Australian unions’ servicing and organizing strategies, and for their future growth prospects.